El sistema de control interno y su incidencia en el área de logística y control patrimonial de la Municipalidad Distrital de Marcabal en el año 2016 - Amador Fernández, Nestor Wilder (2017)
This research addresses the incidence of internal control in the area of logistics and Patrimonial control of the district municipality of Marcabal, under the hypothesis that the implementation of an efficient internal control system in the areas of logistic and Patrimonial control, will contribute to the effectiveness and efficiency of the processes established by the senior management of the district municipality of Marcabal. In the investigation an applied investigation was carried out in reason that for its development in the theoretical part conceptually it supported in knowledge on the system of internal control, in order to be applied in the processes and activities that develop in the areas of logistic and control Patrimonial The population was made up of the 62 servers of the district municipality of Marcabal; this time it was taken as reference for the sample to all the servers of this Institution, being this a relatively small entity, and those who were able to apply the survey, whose results passed through a statistical analysis. The results show a marked difference between the formative level of the servers of the DL 1057 and the servers DL 276; In addition, you can see that there is no functional internal Control office, which has the processes of the institution without adequate control in many of the areas that make up this entity; taking exclusively the area of logistic Control Patrimonial can be observed that the current processes do not have the current regulations , bringing this inconsistencies immediate, which hinders the normal development of activities of the municipal high management, who seek the effectiveness and efficiency of their processes.